A strategic approach to sports crisis management: Assessing the NFL concussion crisis from marketing and public relations perspectives. Issue 3 (5th August 2019) - LaGree, Danielle; Wilbur, Douglas; Cameron, Glen T.
Abstract : Purpose: Using the National Football League (NFL) concussion crisis context, the purpose of this paper is to provide sports marketers with a strategic approach to sports crisis management through consideration of crisis media coverage and organizational reputation. Design/methodology/approach: An online experiment assessed the impact of two crisis response strategies, fan involvement and exposure to crisis media coverage on emotional response, corporate message credibility, crisis perception and perceived corporate reputation. Findings: The accident response strategy was associated with more favorable perceptions of the NFL and corporate message credibility. Sports fan involvement facilitated more favorable perceptions of the NFL's reputation, while exposure to media coverage of the NFL's crisis created negative perceptions of the NFL's reputation. Exposure to media coverage of the NFL concussion crisis increased feelings of anger, which in turn decreased perceptions of corporate message credibility. Research limitations/implications: A limitation for this study is the specific crisis scenario that was used. The NFL concussion crisis is different from other crisis types in that it does not directly impact the audience's well-being, but instead affects their perceptions of an iconic institution. Practical implications: In light of study findings, it is suggested that sports marketers consider the following when dealing with crises: carefully determine proper framing methods when crafting a crisis response as different response types affect consumers in different ways; leverage public relations (PR) practices by engaging in media monitoring to inform an appropriate crisis response to control the narrative; and examine forces exernal of the organization that influence consumer emotions, paying special attention to feelings of anger as anger negatively impacts consumer perceptions of corporate credibility. Originality/value: This paper addresses sports crisis strategy from both marketing and public relations perspectives. It describes how strategic efforts protect a sports organization's reputation, thus increasing marketing effectiveness.